The dynamics of tourism village development: The development of ‘Sumber Jenon’ tourism through the lens of Lefebvre space production theory - Nur Fatimah, Sekar Wulan Noventyas (Direktorat Riset dan Pengabdian kepada Masyarakat UNY, 2025)
: Sumber Jenon is one of the natural attractions in Malang Regency. Tourism which is managed directly by BUMDes Lumbung Argo Tirto in its development through various dynamics that also involve the community. This study focuses on the dynamics of Sumber Jenon's tourism development, and will then be analyzed with Henri Lefebvre's space production concept. In an effort to obtain data, researchers use data collection techniques in the form of interviews, observations and documentation. This research uses qualitative methods with a case study approach. The analysis in this study uses Lefebvre's space production glasses which have three main concepts, namely spatial space, spatial representation and representation space. The results obtained in this study show that in tourism development there is a dynamic, where dynamics arise due to differences in interests between various groups. The dynamics that arise not only aim to fight over material aspects, but also non-material aspects such as public image. The construction of the Jenon Source can be classified into three stages. The stages can be further analyzed using Lefebvre's three concepts of space.